2017
DOI: 10.1007/s11746-017-3038-3
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and thermal characterization of seed oil from Mexican mamey sapote (Pouteria sapota)

Abstract: The aim of this research was to perform a physicochemical characterization of native mamey sapote seed oil [Pouteria sapota (Jacq.) H.E. Moore and Stearn]. Mamey sapote seed oil showed good oxidative stability as it had low peroxide, free fatty acid, and p‐anisidine values. The main fatty acids present in the oil were palmitic, stearic and oleic acid, constituting five major triacylglycerides families: PLP, POP, StOO, POSt and StOSt. Crystallization and melting points of the oil were −37.7 and 23.84 °C, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 27 publications
0
7
2
Order By: Relevance
“…In the case of free fatty acid content (0.55-0.57%), the results are lower than those reported by Hernández-Santos et al (2017); they found 1.88% of free fatty acid in OMSS [20]. This is an excellent result for an oil which has not been subjected to a refining process, especially considering that the degree of edibility of an oil is generally considered to be inversely proportional to the total amount of free fatty acids [20,86]. In the case of the iodine values (56.77-57.40 g/100 g), the results obtained were lower than those reported by Moo-Huchin et al (2103) (174 g/100 g) [18], which suggest a lower content of unsaturated fatty acid [71,87], but in general, OMSS contains a high proportion of monounsaturated and saturated fatty acids in comparison with polyunsaturated fatty acids, so low iodine values are to be expected [20].…”
Section: Some Physicochemical Properties Of the Obtained Oilscontrasting
confidence: 67%
See 4 more Smart Citations
“…In the case of free fatty acid content (0.55-0.57%), the results are lower than those reported by Hernández-Santos et al (2017); they found 1.88% of free fatty acid in OMSS [20]. This is an excellent result for an oil which has not been subjected to a refining process, especially considering that the degree of edibility of an oil is generally considered to be inversely proportional to the total amount of free fatty acids [20,86]. In the case of the iodine values (56.77-57.40 g/100 g), the results obtained were lower than those reported by Moo-Huchin et al (2103) (174 g/100 g) [18], which suggest a lower content of unsaturated fatty acid [71,87], but in general, OMSS contains a high proportion of monounsaturated and saturated fatty acids in comparison with polyunsaturated fatty acids, so low iodine values are to be expected [20].…”
Section: Some Physicochemical Properties Of the Obtained Oilscontrasting
confidence: 67%
“…Acid value of OMSS (1.09-1.12 mg KOH/g) was lower than that reported by Moo-Huchin et al ( 2013), who obtained an acid value of 4.44 ± 2.19 mg KOH/g [18], but in both cases, the acidity of OMSS can be considered low for unrefined oils, and show that they are potentially edible oils [18]. In the case of free fatty acid content (0.55-0.57%), the results are lower than those reported by Hernández-Santos et al (2017); they found 1.88% of free fatty acid in OMSS [20]. This is an excellent result for an oil which has not been subjected to a refining process, especially considering that the degree of edibility of an oil is generally considered to be inversely proportional to the total amount of free fatty acids [20,86].…”
Section: Some Physicochemical Properties Of the Obtained Oilscontrasting
confidence: 54%
See 3 more Smart Citations